Prevalence of Temporomandibular Disorder Symptoms, Oral Behaviors and Depressive Symptoms in the University of the Philippines Manila College of Dentistry Community/ Rossa Ynez B. Cabrera. - Cabrera, Rossa Ynez B.; Bautista, Cesar M. (2019)
INTRODUCTION: Temporomandibular disorders (TMD) are considered a public health
concern. This study determined the prevalence of TMD symptoms, oral behaviors, and
depressive symptoms in a public university, a microcosm of the Filipino population,
following the biopsychosocial model.
METHODS: A cross-sectional study with 239 participants, composed of students, faculty,
and non-academic personnel, out of the total population of 324, answered questionnaires
from the Diagnostic Criteria for Temporomandibular Disorders, namely Symptom
Questionnaire (for the TMD symptoms), representing the biological factor, and Oral
Behaviors Checklist (for oral behaviors), and Patient Health Questionnaire – 9 (for
depressive symptoms), representing the psychosocial factor. Descriptive statistics were
used, specifically frequency distribution.
RESULTS: Of the 239 participants, 46.44% show TMD symptoms, 40.59% manifest oral
behaviors and 54.39% experience depressive symptoms. Three percent exhibited both
TMD symptoms and oral behaviors, 11.29% with both TMD and depressive symptoms,
and 22.17% presented all factors. The condition exists more in females (30.13%) than
males (5.44%). Participants aged 18-30 lead with 31.80%, followed by 31-50 age group
with 2.51%, and least occurring 1.26% in the fifty-one years and above age group.
CONCLUSION: The prevalence of biological and psychosocial factors of TMD among
Filipinos in the University of the Philippines Manila College of Dentistry (UPM CD)
Community is 36.40%.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Temporomandibular joint; Temporomandibular joint--Diseases.